PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERMUATAN MATERI PERTUMBUHAN DAN PERKEMBANGAN MANUSIA PADA PEMBELAJARAN IPA KELAS III SD - Siti Mulyani; Muhammad Iqbal Arrosyad; Vika Martahayu (Universitas Muhammadiyah Bangka Belitung, 2025)
This research is motivated by students having obstacles in understanding the correct concepts in students because these concepts are often memorized, the learning atmosphere is boring and the use or delivery of material by teachers is not as optimal as possible. This research aims to develop an interactive e-module assisted by the Canva application that is valid, practical, and effective on photosynthetic materials in grade IV of elementary school. This type of research is Research and Development (R&D). With the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. The subject of the study was 28 students in grade IV of SD Negeri 1 Simpangkatis. Data collection techniques are interviews, questionnaires, and documentation. Based on the results of the research, 94.4% of media expert validators were obtained with the very valid category, 1 75% with the valid category, and 2 material experts 93.7% with the very valid category. The results of the small-scale trial of 8 IV students were obtained 90.9% with the very practical category and the results of the large-scale trial of 20 students were obtained 94.8% with the very practical category. The average pretest score was 55.71 and the average posttest score was 85.35. The results of the calculation of the pretest and posstest T-Table Test were obtained 12,345 and the results of the pretest and posstest Ttable Test were obtained 1,703 with the information that Ha was rejected and Ha was accepted. The results of the study show that the interactive e-module assisted by the Canva application of photosynthesis material in grade IV of elementary school is valid and very practical to use as a learning process